ALJABAR SL(2,C) DALAM SISTEM INTEGRABEL BERBASIS PERSAMAAN SCHROEDINGER NON-LINIER - Alatas, Husin
Abstrak: We considered integrable system based on the Non-Linear Schroedinger Equation (NLS ) with additional term yru - iEuzux . By using Wahlquist-Estabrook method, this system has the algebraic stricture SL(2,C) with minimal vectors quantity. In order to satisfy the integrability, the system requires the constrain u(x,t)u(x,t)= constant. With this constrain the solution space becomes restricted. We discussed a simple solution in the form of monochromatic wave that satisfies this constrain. In the appendix, we also discuss the NLS equation with i8u term.